A Changed Taxonomy Of Retail Financial Ratios - Zeller, Thomas L.; Kostolansky, John; Bozoudis, Michail (Journal of Applied Business Research, 2017)
Thirty-five years ago researchers established a taxonomy of retail financial ratios. During the intervening period, extensive changes in retailing practices have been accompanied by equally extensive changes in financial reporting, marketing and management methods. Financial reporting standards have adapted to reflect these new domestic and international business practices, while technological innovation has produced continually evolving hardware and software advancements. This study investigates the extent to which the taxonomy of retail financial ratios has changed and, if justified, will establish a revised taxonomy. It extends prior work in two ways. First, it utilizes advanced statistical methodologies and computing technologies to provide a more discriminating investigation than previous researchers were capable of conducting. Second, this study investigates the current taxonomy of retail industry financial ratios as well as its stability over a ten-year period. Our findings identify a shift in the retail sector taxonomy of financial ratios. Empirical analysis points to a taxonomy consisting of five factors: capital intensiveness, cash position, inventory turnover, return on assets-return on sales, and return on equity-leverage. Contrary to expectations, a separate operating cash flow factor was not identified, despite the emergence of a mandatory cash flow statement during the intervening period. These findings provide an empirical basis to formulate testable hypotheses regarding the predictive and descriptive utility of retail financial ratios.